STUDI DESKRIPTIF TANTANGAN PEMBELAJARAN BISNIS KOPI SECARA DARING - Muhammad Setiawan Kusmulyono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The coffee industry is a positive growth business that offers attractive job prospects for coffee-producing countries around the world. This demonstrates the importance of coffee as a global commodity as well as a national economic engine. The expansion of the coffee industry encourages the expansion of other industries, one of which is learning about the coffee industry. Face-to-face learning has unfortunately been displaced by online learning as a result of the pandemic, resulting in some learning methods not being implemented efficiently. This study takes a descriptive method to determine what potential and obstacles exist in online learning about the coffee industry, as well as what coffee subjects might be researched further. The resource persons are 36 students enrolled in the Coffee Business and Management course who completed an open-ended questionnaire. The data was then descriptively evaluated in order to derive conclusions which expressed that challenge of learning in pandemic is higher than the opportunity whereas there is sixteen coffee topics that need to be explored deeper into the learning.